I IMPLEMENTASI PROGRAM PEER TEACHING SEBAGAI UPAYA PENINGKATAN MUTU LULUSAN SISWA DI MADRASAH ALIYAH SWASTA (MAS) UMMUL QURO AS-SUYUTY PAMEKASAN: IMPLEMENTASI PROGRAM PEER TEACHING SEBAGAI UPAYA PENINGKATAN MUTU LULUSAN SISWA DI MADRASAH ALIYAH SWASTA (MAS) UMMUL QURO AS-SUYUTY PAMEKASAN - Ali Nurhadi; Imdadur Rohman (LP2M IAIN Sultan Amai Gorontalo, 2025)
The peer teaching program is an effort to improve the quality of graduates with existing learning innovations. The principal is the main key in the implementation and planning of the peer teaching program. This study aims to describe the implementation, supporting factors, and results of the implementation of the peer teaching program as an effort to improve the quality of student graduates at the Ummul Quro As-Suyuty Pamekasan Private Islamic Senior High School (MAS). The author uses a qualitative approach research method with a descriptive research type to conduct a study. The results of this study state that the implementation of the peer teaching program is carried out at the end of each semester before graduation. Final year students are given the opportunity to carry out teaching/peer teaching practices directly in class. The implementation stages start from selecting material titles through meetings, intensive guidance with teachers, material improvements, scheduling teaching practices, implementing teaching in real classes, assessments from various parties, to final evaluations carried out through meetings. This new finding from the peer teaching program compares favorably with other institutions. The Ummul Quro As-Suyuty Pamekasan Private Islamic Senior High School (MAS) has been in existence since its inception, employing distinctive Islamic materials including Nahwu (National Language), Mahfodzat (Quotes), English, and story-based Arabic (Qiraatu al-Rasyidah). This has become a distinctive feature of the institution in implementing a peer teaching program tailored to students' needs.